Active control of friction in electrified ball bearing prototypes using electro-sensitive clay mineral-based lubricating fluids - Samuel David Fernández-Silva; Miguel Ángel Delgado; Claudia Roman; Tobias Amann; Felix Gatti; Andreas Kailer; Moisés García-Morales (Friction)
The aim of this research is to present the use and advantages of electro-active eco-fluids as smart biolubricants. Polarizable clay mineral nanoparticles, such as the layered nanosilicate montmorillonite Cloisite 15A and the fiber-like sepiolite Pangel B20, were dispersed in a sustainable fluid, castor oil, at concentrations of 0.5, 2, and 4 wt%. These dispersions exhibit electro-viscous behavior, which was characterized by higher yield stress values with increasing electric field strength. Based on this, the influence of electric potentials was investigated in an electrified axial ball bearing device. The coefficient of friction (COF) was changed as needed and reversibly when different electric fields of 100 and 200 V/mm were applied. A 10.7% increase in the coefficient of friction was observed with a 4 wt% Cloisite 15A in castor oil at 200 V/mm. In the case of Pangel B20, the application of an electric field of 200 V/mm successfully prevented the lubricant from being displaced from the contact zone at 500 r/min. In addition, the dielectric breakdown resistance of these clays was analyzed. Cloisite 15A yielded better results than Pangel B20, probably due to its greater electro-responsive and thus film-forming potential. Finally, the load-carrying capacity was also evaluated. Under the action of an electric field, an opposite vertical force was observed when a ball was pressed onto a plate with a lubricating film in between. Consequently, the study allows conclusions to be drawn about a new lubrication concept based on electro-active control of friction in electrified tribological contacts by fully sustainable electro-rheological (ER) lubricating fluids.